THREEFOLD PROPERTIES OF SPEECH SOUNDS: ARTICULATORY, ACOUSTIC, AND AUDITORY PERSPECTIVES - Teshaboyeva Nafisa Zubaydulla qizi; Xidirova Dilnoza Nurali qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Speech sounds, fundamental to human communication, can be analyzed through three primary dimensions: articulatory, acoustic, and auditory properties. This tripartite model provides a framework for understanding how sounds are produced, transmitted, and perceived in human languages. Each property offers unique insights: articulatory properties explore how speech organs generate sounds; acoustic properties analyze sound waves as they propagate; and auditory properties investigate how sounds are received and interpreted by listeners. This paper examines each of these dimensions, presenting insights from phonetics and cognitive linguistics, to outline a comprehensive model of speech sound properties.